Direct and indirect effects of science management policy capacity framework on results of science and technology management activities in Vietnam - Tran Quang Huy; Tu Thao Huong Giang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Human Resource Development for Science, Technology and Innovation (STI) has been discussed by several scholars and previous studies show that competency framework forecasting management performance. However, lack of empirical reseach verified the self-efficacy as a mediator to enhance the extreme performance in STI state management with competency framework. This study analyze how policy competency framework affects management performance in Vietnam, especially emphasizing self-efficacy as an important mediator. A survey of 188 officers from the Ministry of Science and Technology, Vietnam targeted at managers and seniors was conducted. We used Confirmation Factor Analysis (CFA) and Structure Equation Model (SEM) to analyze the latent variables, research model and confirm the hypotheses. The finding implies that policy competency framework including policy making, implementation and evaluation associates with state management performance. This relation is also mediated by self-efficacy for policy makers to achieve excellence management performance. Code: 23021302